2017
DOI: 10.1002/adhm.201700202
|View full text |Cite
|
Sign up to set email alerts
|

Timed Delivery of Therapy Enhances Functional Muscle Regeneration

Abstract: Cell transplantation is a promising therapeutic strategy for the treatment of traumatic muscle injury in humans. Typically, previous investigations have focused on the identification of potent cell and growth factor treatments and optimization of spatial control over delivery. However, the optimal time point for cell transplantation remains unclear. Here we study how myoblast and morphogen delivery timed to coincide with specific phases of the inflammatory response affects donor cell engraftment and the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Immediately after vessel ligation, the calf muscle of the ischemic limb, consisting of the gastrocnemius, plantaris, and soleus muscles, was injected with 50 μL of the alginate gel, consisting of concentrated CM from 2 million T-cells. Injection into the distal limb was done to simultaneously induce angiogenesis and myogenesis in the degenerating ischemic skeletal muscle in the distal limb, as previously described [21, 22]. At days 3 and 6 after vessel ligation, the injections were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after vessel ligation, the calf muscle of the ischemic limb, consisting of the gastrocnemius, plantaris, and soleus muscles, was injected with 50 μL of the alginate gel, consisting of concentrated CM from 2 million T-cells. Injection into the distal limb was done to simultaneously induce angiogenesis and myogenesis in the degenerating ischemic skeletal muscle in the distal limb, as previously described [21, 22]. At days 3 and 6 after vessel ligation, the injections were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the complexity of the healing cascade and its precise spatiotemporal regulation, it is unlikely that a single molecular factor is able to rescue a tissue from degeneration. Thus, the timed delivery of multiple growth factors could be required . In this regard, Borselli et al .…”
Section: Advances In Treatment Of Local Muscle Injuriesmentioning
confidence: 99%
“…Thus, the timed delivery of multiple growth factors could be required. 89 In this regard, Borselli et al have shown that the simultaneous delivery of myogenic (IGF-1) and angiogenic growth factors (VEGF) can promote functional regeneration of ischaemic muscle tissues. 90 However, it is pertinent to note that while this combination of growth factors demonstrated significant benefit in ischaemia, no apparent benefit was observed with the same dose of growth factors in a crush muscle injury model.…”
Section: Molecular Therapiesmentioning
confidence: 99%
“…12 The biological activities of silicate ions relied on their release kinetics from the SRH, 36 which was tested by immersing samples in deionized water for up to 7 days and the critical time period for the delivery of therapy to enhance muscle regeneration. 37 All hydrogels showed an efficient release of silicate ions on the first day (Fig. 2D) when minimal degradation occurred, indicating the ease of silicate ion transport through the hydrogel network.…”
Section: Srh Preparation and Characterizationmentioning
confidence: 91%